What is Online Research? - Tristram Hooley; Jane Wellens; John Marriott (Bloomsbury Academic, 2012)
What is Online Research? is a straightforward, accessible introduction to social research online. The book covers the key issues and concerns, with sections on design,ethics and good practice. It will be key reading for social scientists of all levels.
English